(untitled) (Research, Society and Development, 2021)
Objective: To characterize the profile of Community Health Workers, and to identify the processes that facilitate and hinder the work of CHWs. Method: The analysis of the empirical material from semi-structured interviews, with CHWs from the city of Campina Grande-PB, Brazil, chosen in a non-probabilistic and convenient way, carried out from May 2018 to August 2019, was carried out through content analysis of Bardin, and its categorization from Iramuteq 0.6. The study had a descriptive-exploratory character, with a qualitative, systematic and subjective approach. This research was approved by the Research Ethics Committee (CEP) of the Hospital Universitário Alcides Carneiro, CAAE n 65858717.9.00005182. Results: In the statements of the CHWs, it is identified that they recognize their importance as agents that facilitate the service, linking UBS and the community, in addition to their educational role and their experienced and intimate knowledge to users. On the other hand, they reinforce difficulties such as lack of PPE, difficulties in dealing with domestic violence, and in the community, there is a lack of vaccines and other inputs, and a lack of management support. Conclusion: In summary, the lack of articulation in the service proves to be the greatest obstacle to the effectiveness of assistance to the community through CHWs.